2023
DOI: 10.1109/tvt.2022.3229822
|View full text |Cite
|
Sign up to set email alerts
|

Max-Min Fairness of Rate-Splitting Multiple Access With Finite Blocklength Communications

Abstract: Rate-Splitting Multiple Access (RSMA) has emerged as a potent and reliable multiple access and interference management technique in wireless communications. While downlink Multiple-Input Multiple-Ouput (MIMO) RSMA has been widely investigated, uplink MIMO RSMA has not been fully explored. In this paper, we investigate the performance of uplink RSMA in short-packet communications with perfect Channel State Information at Transmitter (CSIT) and Channel State Information at Receiver (CSIR). We propose an uplink M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In [49], the authors proposed a flexible RSMA scheme for a MISO BC with FBL and showed that their proposed scheme outperforms SDMA and NOMA. In [50], [51], it was shown that RSMA can achieve the same minimum or sum rate as NOMA and SDMA with a smaller packet length, meaning that RSMA may reduce latency for a given target rate. In [52], the authors proposed resource allocation schemes for RSMA in a MISO URLLC BC, showing that RSMA provides a higher effective throughput than NOMA.…”
Section: A Related Workmentioning
confidence: 99%
“…In [49], the authors proposed a flexible RSMA scheme for a MISO BC with FBL and showed that their proposed scheme outperforms SDMA and NOMA. In [50], [51], it was shown that RSMA can achieve the same minimum or sum rate as NOMA and SDMA with a smaller packet length, meaning that RSMA may reduce latency for a given target rate. In [52], the authors proposed resource allocation schemes for RSMA in a MISO URLLC BC, showing that RSMA provides a higher effective throughput than NOMA.…”
Section: A Related Workmentioning
confidence: 99%
“…RSMA outperforms other multiple access techniques by offering greater flexibility and powerful interference management capabilities [10]. In downlink RSMA, numerous studies have focused on optimizing the transmission power and precoding vectors for both the common and private signals to achieve various objectives, such as sum-rate maximization [10,[13][14][15], max-min rate fairness [16,17], and energy efficiency maximization [11,18]. The symbol is used to denote that an aspect is included in the study, while indicates that it is not.…”
Section: Related Workmentioning
confidence: 99%
“…Different from the previous studies, we focus on a multi-antenna FlyBS with RSMA that can fly along a 3D trajectory while providing communication services to mobile ground users. The multi-antenna technology has been extensively employed in groundbased BSs [10,11,[13][14][15][16][17][18]. By leveraging the benefits of increased signal strength, expanded coverage, reduced interference, and beamforming capabilities, multi-antenna arrays can provide reliable and high-quality wireless services.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [ 21 ] investigated RSMA in short-packet communication and demonstrated that RSMA with smaller block lengths achieves the same maximum–minimum fairness rate as NOMA and space division multiple access (SDMA). Ref.…”
Section: Introductionmentioning
confidence: 99%